Atheism and Theism - Harris, E.E. author. aut Link
XII, 157 p.
Keywords: Professor Errol E. Harris presented the first three chapters of Atheism and Theism as public lectures at Tulane University on January 20-22, 1975. The lecture series was made possible by a grant from the Franklin J. Matchette Foundation of New York City. Those of us who had the pleasure of hearing the lectures formed the judgment that they deserved publication to reach a wider audience and to assure a more permanent reeord. We invited Professor Harris to allow us to publish his lectures in Tulane Studies in Philosophy. On his part, he de veloped the themes of the lectures into a more comprehensive and lasting work. With Professor Harris's approval, we are taking the unprecedented step of devoting Volume XXVI of Tulane Studies in Philosophy to the publication of Atheism and Theism. We are certain that it will advance the fundamentally philosophical argument surrounding theism and Christianity. We are also convinced that it will add substantialIy to the prestige of our series of annua1 volumes of philosophy, now in its twenty-sixth year. 'Ve wish to express our thanks to the Franklin J. Matchette Foundation for the original grant sup porting the lectures and to Professor Harris for presenting first the lectures and then the book. R. C. W. A. J. R.